Comprehensive Transcriptome Analysis of mRNA Expression Patterns Associated With Enhanced Biological Functions in Periodontal Ligament Stem Cells Subjected to Short-Term Hypoxia Pretreatment - Li, Zhi-Bang; Yang, Hui-Qi; Li, Kun; Yin, Yuan; Feng, Su-Su; Ge, Shao-Hua; Yu, Yang (Frontiers in Genetics, 2022)
Short-term hypoxia pretreatment significantly enhances periodontal ligament stem cell (PDLSC)-based periodontal tissue regeneration by improving various cellular biological functions, but the underlying mechanisms remain unclear. In this study, based on RNA sequencing (RNA-seq), we comprehensively analyzed the possible regulatory mechanisms of the short-term hypoxic effects on the biological functions of healthy and inflammatory PDLSCs. A total of 134 and 164 differentially expressed genes (DEGs) were identified under healthy and inflammatory conditions, respectively. Functional enrichment analyses indicated that DEGs under both conditions share certain biological processes and pathways, including metabolic processes, developmental processes, reproductive processes, localization, immune system processes and the HIF-1 signaling pathway. The DEGs identified under inflammatory conditions were more significantly enriched in cell cycle-related processes and immune-related pathways, while DEGs identified under healthy condition were more significantly enriched in the TGF-β signaling pathway. A protein-protein interaction network analysis of the 59 DEGs in both conditions was performed, and 15 hub genes were identified. These hub genes were mainly involved in glycolysis, the cellular response to hypoxia, cell differentiation, and immune system processes. In addition, we found that hypoxia induced significant differential expression of genes associated with proliferation, differentiation, migration, apoptosis and immunoregulation under both healthy and inflammatory conditions. This study provides comprehensive insights into the effects of short-term hypoxia on the biological functions of PDLSCs and suggests a potentially feasible strategy for improving the clinical effectiveness of cell-based periodontal tissue engineering.